Influence Of Different NPK Levels On The Impact Of Growth And Development Of Sweet Orange (Citrus Sinesisosbeck) Plants (International Journal of Food and Nutritional Sciences, 2021)
The present investigation entitled Effect of different levels of Nitrogen (N) Phosphorus (P2O5) and Potassium (K2O) on growth and development of Sweet Orange (Citrus sinesis Osbeck) plants were carried out at Fruit Research Farm, Rama University, Kanpur (2019).The results revealed that the treatment T3 (350 g / plant Nitrogen, 250 g / plant Phosphorus and450 g / plant Potash)was found to be the best in terms of maximum plant height (83.57cm), maximum number of leaves (421.04), maximum number of branches (26.36), maximum stem diameter (3.04 cm), maximum spread of canopy(42.36 cm)and maximum length of inter-nodes (9.68cm) followed by treatment T9 (300 g / plant Nitrogen, 250 g / plant Phosphorus and500 g / plant Potash) and the minimum was recorded in T12(300g / plant Nitrogen, 250g / plant Phosphorus and 300g / plant Potash).